If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 2 = 3x + 27 Reorder the terms: 2 + 8x = 3x + 27 Reorder the terms: 2 + 8x = 27 + 3x Solving 2 + 8x = 27 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2 + 8x + -3x = 27 + 3x + -3x Combine like terms: 8x + -3x = 5x 2 + 5x = 27 + 3x + -3x Combine like terms: 3x + -3x = 0 2 + 5x = 27 + 0 2 + 5x = 27 Add '-2' to each side of the equation. 2 + -2 + 5x = 27 + -2 Combine like terms: 2 + -2 = 0 0 + 5x = 27 + -2 5x = 27 + -2 Combine like terms: 27 + -2 = 25 5x = 25 Divide each side by '5'. x = 5 Simplifying x = 5
| 4=7x-10 | | 4(7-x)=5(x-2) | | 4x+9=51-2 | | 5-7x=37+4x | | 30+x=9x-10 | | 7a+10=-3a | | 48-3x=6x+17 | | (k+2)2w^2+4w+6=0 | | 193-6x=6x+30 | | 5*x+16*y=789 | | 6x-3=15x | | 2(i-3)=14 | | 6p=3p+30 | | 2g-3=1 | | 6x-4=3x+10 | | 3x+5-(2x+1-(2x-3-(x-2)))=x+15 | | 106-5x=22+22 | | 3u^2=11u+4 | | 4a+8=6(a+4) | | 17x+4y=67 | | 30-3x=6-3x | | 3a+4b=12 | | 3x-3v=3t | | x^2+14x=4 | | .5x=12+2x | | 6x+10=78x+x | | -17+-10*x=10+23 | | 10x-11=8+3 | | X^2-8X=17 | | 7x=24+39 | | 58-6x=3x+17 | | 3x^2y-9xy-12y= |